Optimization of aphanamixis based biodiesel and its combustion characteristics / Md. Ruhul Amin - Md. Ruhul , Amin (2017)
A non-edible vegetable oil source “Pithraj” widely known as “Aphanamixis polystachya” (AP) was chosen in the current study considering the high price of edible oil sources and food security. Main forces of this study were to optimize the biodiesel production process from low-quality vegetable oil employing waste eggshell extracted heterogeneous catalyst and evaluate fuel feasibility in an unmodified diesel engine. A heterogeneous catalyst was extracted and confirmed its activity as a catalyst by various characterization like thermogravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy analysis, scanning electron microscope (SEM), energy dispersive X-ray (EDX) spectroscopy and X-ray powder diffraction (XRD) analysis. The basic strength of the Egg CaO catalyst found to be 9.8<H_<10.1 which is very close to commercially available Pure CaO. This heterogeneous catalyst was introduced at the transesterification step to produce biodiesel which is cost effective as well as eco-friendly. Both the esterification and transesterification chemical process for biodiesel yield was optimized through response surface methodology (RSM). Product yield after degumming stage, esterification and transesterification stage were found 97.12%, 96.53% and 97.5% respectively, which is 91.4% of crude oil. When optimal reaction condition for esterification was 152.79 % (v/v of oil) methanol, 0.80% (v/v of oil) catalyst loading and 60.29 °C reaction temperature for 3 hours. The optimal condition for transesterification was found at 35.59 % (v/v of esterified oil) methanol, 1.46% (w/w of esterified oil) catalyst loading and 65.10 °C reaction temperature for 2 hours. Properties of the biodiesel and its blends with diesel conform the ASTM specification. Finally, the produced biodiesel blends were tested in a single cylinder diesel engine at various operating condition such as (a) constant torque, variable engine speed (b) constant speed, variable torque and (c) constant speed with advancing and retarding injection timing. Combustion, performance and exhaust gas emission characteristics were investigated by 20% (v/v) and 30% (v/v) biodiesel-diesel blends and compared with ordinary diesel (OD) as well as the corresponding blends of “Millettia pinnata” biodiesel. AP diesel-biodiesel blends provide slightly decreased brake power (BP), brake thermal efficiency (1.22-0.33%) and increased brake specific fuel consumption (about 1.17-2.09%) compared to OD. In-cylinder pressure (ICP), heat release rate (HRR), mass fraction burned (MFB) and ignition delay (ID) were found to inferior in quality for AP on OD. The average CO and HC emissions were reduced to an extent of 13.90-14.27% and 4.03-10.09% for AP biodiesel blends, whereas NO, CO2 emission was found to be 2.93-5.47% and 8.61-17.23% respectively, higher than OD.